FORMULASI SEDIAAN GEL SCRUB WAJAH SERBUK BIJI KOPI ARABIKA (Coffee arabica) DENGAN KONSENTRASI KARBOPOL 940 SEBAGAI GELLING AGENT - Natasha Faruqi Andrian Putri; Desy Nawangsari; Sunarti Sunarti (Jurnal Farmasi & Sains Indonesia, 2021)
ABSTRACT Coffee is a plant that is rich in benefits. Arabica coffee beans contain antioxidants that can provide benefits, one of which is preventing cell damage due to exposure to free radicals. Arabica coffee is formulated in the form of a gel scrub with the gelling agent carbopol 940. This study aims to determine the best concentration of gelling agent on the physical properties and stability of the Arabica coffee bean gel scrub and when used it causes irritation or not. Pure experimental research method to determine the effect of certain treatments by comparing with the control group that was not given treatment. Evaluation of gel scrub preparations included evaluation of the physical quality of the preparation and irritation test on 3 rabbits. The results of the evaluation of the preparations showed that all gel scrub preparations were in the form of a gel with black granules, distinctive smell, homogeneous, stable during 6 cycles of storage, pH value (4.5-7.8), adhesion (2-300 seconds), spreadability (5-7 cm) and viscosity (2000-4000 cp), irritation test in rabbits caused a slight irritating skin reaction. The results of the statistical test with the one way anova test showed that there was a significant difference between the formulas with a significance value (p < 0.05). However, the stock can still be said to be stable because it is still in the range of requirements. In conclusion, the gel scrub produced has good physical characteristics and causes a slight irritation of the skin reaction. Arabica coffee bean powder can be formulated as a gel scrub preparation which has good physical characteristics in formula IV with a concentration of carbopol 940 2%. and stable at 6 cycles of storage.